Cell Density-Mediated Pericellular Hypoxia and the Local Dynamic Regulation of VEGF-A Splice Variants in Ovine Ovarian Granulosa Cells. Issue 2 (1st August 2014) - Marsters, Peter; Alhamdan, Rana; Campbell, Bruce K.
Abstract: The primary aims of this study were to utilize a specialized culture system to further elucidate the functional significance of pericellular hypoxia within the granulosa cell (GC) compartment of growing follicles, and to clarify its effects on the production of vascular endothelial growth factor (VEGF)-A isoforms and steroid hormones. Multilaminar clusters formed rapidly in ovine GCs seeded at high density (HD), and Hypoxyprobe-1 protein adducts appeared markedly more abundant and HIF-1 activation significantly ( P < 0.001) greater than in cells seeded at low density (LD). Four proangiogenic VEGF mRNA transcript variants were identified in cultured GCs. Most abundant were VEGF120 and VEGF164, but VEGF182 and VEGF188 were also detected. Total VEGF mRNA was shown to be up-regulated transiently in the HD cells ( P < 0.001) and VEGF164 mRNA appeared to contribute most to this. The hypoxia mimetic cobalt chloride also induced marked increases in HIF-1 activation ( P < 0.01) and total VEGF mRNA ( P < 0.01) production. HD cells increased levels of HIF-1alpha ( P < 0.001) and VEGF receptor type 1 ( P < 0.05), but not VEGF receptor type 2 mRNA, compared to LD cells or cells grown under chemically induced hypoxia. Both 17beta-estradiol (E2) and progesterone (P4) were markedly lower ( P < 0.001) in the HD, cells but though cobalt chloride treatment accompanied significantly reduced P4 production ( P < 0.05), E2 levels remained similar to those in untreated cells. These outcomes suggest that pericellular hypoxia may be an important mediator of VEGF production in the GCs of growing follicles, but that local regulation is complex and may involve multiple mechanisms such as mediation by steroid hormones and differential variant mRNA production.